Method and equipment for the safe development of preparatory workings in the gas-bearing coal seams - Trokhymets Mykola; Maltseva Vira; Vialushkin Yehor; Antonchik Volodymyr; Moskalova Tetiana; Polushyna Maryna (E3S Web of Conferences, 2019)
The article describes a method and equipment for the safe development of preparatory working on a gas-bearing, outburst hazardous coal seam by a heading machine. The described method significantly prevents the gas emission during mining operations. Determination of the amount of degassing and relief wells is performed according to the given in article mathematical formulas. This ensures a significant increase in the level of safety processing the preparatory roadway on a gas-bearing, prone to outbursts coal seam by a heading machine. Due to this, the speed of conducting excavation increases and the cost of mining is reduced. The proportionality coefficients of the mathematical models were determined. Mathematical models are used to calculate the number of relief and degassing wells, which are drilled during the impulse hydraulic loosing of the nearby part of the coal seam. Also the duration of liquid injection into a coal seam is also determined. Mathematical models for calculating the number of injection, unloading and degassing boreholes can be used in development of the passports for conducting preparatory workings on a gas-bearing, prone to outburst coal seam by a heading machine with a preliminary impulse hydraulic loosing of the nearby part of a coal seam.